MEMPERTAHANKAN TANAH AIR PALESTINA PADA PUISI “QAṢĪDATU AL-ARḌI” DALAM ANTOLOGI AL-AʻMĀLU AL-KĀMILATU KARYA MAḤMŪD DARWĪSY ANALISIS SEMIOTIK - Ridhotun Ni’mah (CMES (Center of Middle Eastern Studies), 2019)
The condition of Palestine which has been occupied by Israel for a long time and has yet to be resolved, encourages poets to give birth to literary works in which echoed the suffering experienced by the Palestinian people. One of them is the poem of Maḥmūd Darwīsy entitled "Qaṣīdatu Al-Arḍi" in anthology Al-Aʻmālu Al-Kāmilatu. The poem reflects the message of revealing encouragement for the community in fighting for the Palestinian homeland and bringing up Palestinian nationalism. Therefore, the aim of this study is to uncover the meaning of this poem in relation to defending the Palestinian territories and uniting the nationalism of the people. The theory used in this research is the semiotic theory, which is a discipline that views the poem "Qaṣīdatu Al-Arḍi" in anthology Al-Aʻmālu Al-Kāmilatu as a semiotic marker where the meaning (signified) requires deeper analysis. Methodologically, this study uses the Michael Riffaterre semiotic model, a method that reveals the meaning of poetry technically using indirect expressions, heuristic readings, and hermeneutic readings. The results of this study found that this poem implies the struggle of the Palestinian people in defending their homeland where the action was manifested in large-scale demonstrations but unfortunately it did not even have any impact. Therefore, the only effective way to do it is by telling it through literary works such as in the title "Qaṣīdatu Al-Arḍi" in the anthology of AlAʻmālu Al-Kāmilatu. The work is a reflection of the suffering of the Palestinian people represented by the author, Maḥmūd Darwīsy, a Palestinian writer.